Forty years of midwinter counts of waterfowl along the coasts of Scania, south Sweden, 1964—2003 - Nilsson, Leif (Ornis Svecica, 2005)
The International Midwinter Counts, organised by Wetlands International, started in January 1967, but co-ordinated counts were organised along the coasts of Scania, south Sweden, already since January 1964. This paper summarises the results of the first forty years. During the first years full coverage was attained, but in later years the counts covered nine larger areas, containing about 75% of all waterfowl. Of the more common species, ten showed significantly increasing, four significantly decreasing, and two species no clear trend. National midwinter indices are available for 11 species; in 10 of these the regional trends are similar to the national trends, Scania forming an important part of the national sample. Several of the changes are related to the hardness of the winters, the milder winters making it possible for more waterfowl to winter in Sweden now compared to earlier years. The decreasing trend for Aythya fuligula in Scania is an example of such changes in winter distribution within the country, more individuals now staying in the Baltic archipelagos than earlier.